Optimization of culture conditions for extracellular fungal lipase production by submerged fermentation process - Shreya, .; Sharma, Arun Kumar; Sharma, Vinay; Saxena, Jyoti (Plant Science Today, 2018)
The present study aimed to optimize culture conditions for optimal growth and production of extracellular lipase. Lipolytic fungal strain named as S3St2 previously isolated from a petrol pump soil sample of Newai Town was used for optimization study. Among the tested carbohydrate carbon sources, polysaccharide-starch exhibited maximum lipase production (21.25±0.70 IU/ml/min) with highest specific activity (1.47±0.06 U/mg). Lipase activity and specific activity were higher with mustard oil 1 % (v/v) among all lipidic carbon sources. Among inorganic nitrogen source, potassium nitrate was found best inducer of lipase activity, malt extract supported the fungus growth (dry weight of cell pellets was 0.467 g) and exhibited maximum lipase activity among all organic nitrogen sources. Lipase activity was optimum at pH 8.0, indicates alkalophillic nature of production media supports the growth of fungus. Higher lipase activity (27.92±0.87 IU/ml/min) was detected at 28ºC. The incubation time of 5 days was found optimum for maximum lipase production (31.51±0.21 IU/ml/min).